Mastering wireless penetration testing for highly secured environments : scan, exploit, and crack wireless networks by using the most advanced techniques from security professionals /: scan, exploit, and crack wireless networks by using the most advanced techniques from security professionals. (2015) - Johns, A (Aaron)
No abstract available